Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric device
By doping M' elements into the core of the high-nickel layered positive electrode active material and forming an intermediate layer of porous structure between the core and the shell layer, the problem of volume deformation and cracking of the material during charging and discharging is solved, and its cycling performance is significantly improved.
Patent Information
- Application Number
- CN202311697297.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-09-15
AI Technical Summary
High-nickel layered positive electrode active materials are prone to large volume deformation during charging and discharging, resulting in the risk of internal cracking of the material and affecting the cycling performance of the battery.
The volume stability and cyclic performance of the positive electrode active material are improved by doping the M' element into the positive electrode active material of the core and providing an intermediate layer with a porous structure between the core and the shell layer.
The risk of cracking of the cathode active material particles during the charge and discharge cycle is reduced, and its volume stability and circulation performance are improved.
Smart Images

Figure CN119650611A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of batteries, and more specifically, relates to a positive electrode active material, a method for preparing the same, a positive electrode sheet, a battery, and an electrical device. Background Art
[0002] As an energy storage device, batteries are widely used in various fields. Taking lithium-ion batteries as an example, they have the characteristics of being green, environmentally friendly, high-energy, and low-carbon. They are not only used in energy storage power systems such as hydropower, thermal power, wind power, and solar power plants, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, and ships, as well as in many fields such as military equipment and aerospace. With the development of current society, people's requirements for batteries are also getting higher and higher. Summary of the Invention
[0003] In view of the technical problems in the background art, this application provides a positive electrode active material, aiming to improve the volume stability of the positive electrode active material during charge and discharge and improve the cycle performance of the battery.
[0004] To achieve the above object, the first aspect of this application provides a positive electrode active material, which includes:
[0005] a core, the core includes Li a1 Ni x1 M y1 M′ z1 O m1 R n1 , where 0.9 ≤ a1 ≤ 1.1, 0.6 ≤ x1 < 1, 0 ≤ y1 ≤ 0.4, 0 < z1 ≤ 0.01, 1.9 ≤ m1 ≤ 2.2, 0 ≤ n1 ≤ 0.1; M includes at least one element selected from Co, Mn, Al, Ta, Mg, Mo, Ga, Sn, Ge, Te, La, Ce; M′ includes at least one element selected from Y, La, Mo, Zr, W, Sb, Nb, Te, Sr, Ti, or Ga; R includes at least one element selected from F, Cl, or S;
[0006] an intermediate layer, the intermediate layer covers at least a part of the outer surface of the core, and the intermediate layer has a porous structure;
[0007] a shell layer, the shell layer covers at least a part of the outer surface of the intermediate layer, and the shell layer includes Li a2 Ni x2 M y2 M′ z2 O m2 R n2 , where 0.9 ≤ a2 ≤ 1.1, 0.6 ≤ x2 < 1, 0 ≤ y2 ≤ 0.4, 0 ≤ z2 ≤ 0.01, 1.9 ≤ m2 ≤ 2.2, 0 ≤ n2 ≤ 0.1.
[0008] The positive electrode active material of the present application has the following beneficial effects: the layered positive electrode active material with high nickel content is prone to large volume deformation during the charge and discharge process, and there is a risk of cracking inside the material, and the cracks may extend to the surface of the positive electrode active material particles. By doping the positive electrode active material located in the inner core with the M' element, it is beneficial to improve the volume stability of the inner core of the positive electrode active material during the charge and discharge process, and reduce the risk of cracking inside the positive electrode active material particles; at the same time, by providing an intermediate layer with a porous structure between the inner core and the outer shell layer, it is also beneficial to buffer the volume deformation and stress accumulation of the inner core, and inhibit the cracking inside the positive electrode active material particles and the extension of the cracks to the surface. In this way, the risk of cracking of the positive electrode active material particles during the charge and discharge cycle can be reduced, and its volume stability and cycle performance can be improved.
[0009] In some embodiments of the present application, the intermediate layer includes: M″ p O q , 1≤p≤2, 2≤q≤3, M″ includes at least one element of B, Al or Si. Meeting the given conditions is beneficial to reducing the risk that the intermediate layer material may adversely affect the electrochemical properties of the positive electrode active material, and is also beneficial to combining M″ p O q The formation method forms an intermediate layer with a porous structure in the positive electrode active material, which is beneficial to taking into account both the electrochemical performance and cycle stability of the positive electrode active material.
[0010] In some embodiments of the present application, in the positive electrode active material, the ratio of the molar number of the M" element to the molar number of the Li element is (0.005-0.02): (0.9-1.1). Controlling the relative amounts of the M" element and the Li element to meet the given range is beneficial to further taking into account the high specific capacity and cycle stability of the positive electrode active material.
[0011] In some embodiments of the present application, in the positive electrode active material, the ratio of the molar number of the M″ element to the molar number of the Li element is (0.008-0.012): (0.9-1.1).
[0012] In some embodiments of the present application, z2>0. Ensuring that the outer shell layer satisfies the given conditions is beneficial to further improving the cycle stability of the positive electrode active material.
[0013] In some embodiments of the present application, the kernel includes: Li a1 Ni x1 Co y11 Mn y12 M′ z1 O m1 R n1, 0≤y11≤0.2, 0≤y12≤0.2, y11 and y12 are not 0 at the same time; and / or, the outer shell layer comprises: Li a2 Ni x2 Co y21 Mn y22 M′ z2 O m2 R n2 , 0≤y21≤0.2, 0≤y22≤0.2, y21 and y22 are not simultaneously 0. Meeting the given conditions is conducive to taking into account both the high specific capacity and the cycle performance of the lithium battery.
[0014] In some embodiments of the present application, 0.002≤z1≤0.008; and / or, 0.002≤z2≤0.008. Controlling the values of z1 and z2 to meet the given range conditions is also beneficial to reducing the risk that M′ doping may cause a decrease in the electrochemical performance of the positive electrode active material.
[0015] In some embodiments of the present application, the particle size of the positive electrode active material is D1, the distance from the inner surface of the intermediate layer to the center of the core is greater than or equal to 0.3D1, and the distance from the outer surface of the intermediate layer to the center of the core is less than or equal to 0.4D1. Meeting the given conditions is not only conducive to improving the cracking risk of the positive electrode active material during the cycle process, but also conducive to reducing the negative impact on the ion migration rate and volume energy density, and is conducive to further taking into account the cycle performance, rate performance and energy density of the positive electrode active material.
[0016] In some embodiments of the present application, the particle size of the positive electrode active material is D1, and the thickness of the intermediate layer is 0.05D1 to 0.0625D1. Meeting the given conditions is not only conducive to improving the cracking risk of the positive electrode active material during the cycle, but also conducive to reducing the negative impact on the ion migration rate and volume energy density, and is conducive to further taking into account the cycle performance, rate performance and energy density of the positive electrode active material.
[0017] In some embodiments of the present application, the volume particle size distribution of the positive electrode active material satisfies: Controlling the volume particle size distribution of the positive electrode active material to meet the given conditions is conducive to obtaining a higher compaction density and improving the volume energy density of the battery.
[0018] In some embodiments of the present application, the volume average particle size Dv50 of the positive electrode active material is 6 μm to 18 μm. Meeting the given conditions is not only conducive to improving the stability of the overall structure of the positive electrode active material particles, but also conducive to making the positive electrode active material have the advantages of a small internal conduction distance and few surface side reactions, thereby further improving the electrochemical performance of the positive electrode active material.
[0019] The second aspect of the present application provides a method for preparing a positive electrode active material, which includes:
[0020] Mixing the core raw materials including a nickel source, an M source, and an M' source to obtain a mixed solution, and performing a first precipitation reaction on the obtained mixed solution to obtain first particles;
[0021] Mixing the solution formed by the intermediate layer raw materials with the first particles to perform a second precipitation reaction to obtain second particles;
[0022] Mixing the shell layer raw materials including a nickel source and an M source, and mixing the obtained mixed solution with the second particles to perform a third precipitation reaction to obtain precursor particles;
[0023] Mixing the precursor particles with a lithium source and performing sintering to obtain the positive electrode active material;
[0024] wherein: the precipitation product formed on the outer surface of the first particles during the second precipitation reaction forms a porous structure through the sintering;
[0025] The positive electrode active material includes:
[0026] a core, the core including Li a1 Ni x1 M y1 M' z1 O m1 R n1 , 0.9 ≤ a1 ≤ 1.1, 0.6 ≤ x1 < 1, 0 ≤ y1 ≤ 0.4, 0 < z1 ≤ 0.01, 1.9 ≤ m1 ≤ 2.2, 0 ≤ n1 ≤ 0.1; M includes at least one element of Co, Mn, Al, Ta, Mg, Mo, Ga, Sn, Ge, Te, La, Ce; M' includes at least one element of Y, La, Mo, Zr, W, Sb, Nb, Te, Sr, Ti or Ga; R includes at least one element of F, Cl or S;
[0027] an intermediate layer, the intermediate layer covering at least a part of the outer surface of the core, and the intermediate layer having a porous structure;
[0028] a shell layer, the shell layer covering at least a part of the outer surface of the intermediate layer, and the shell layer including Li a2 Ni x2 M y2 M' z2 O m2 R n2 , 0.9 ≤ a2 ≤ 1.1, 0.6 ≤ x2 < 1, 0 ≤ y2 ≤ 0.4, 0 ≤ z2 ≤ 0.01, 1.9 ≤ m2 ≤ 2.2, 0 ≤ n2 ≤ 0.1.
[0029] The method for preparing positive electrode active materials in the present application has the following beneficial effects: not only can the core including Li a1 Ni x1 M y1 M′ z1 O m1 R n1 , the outer shell includes Li a2 Ni x2 M y2 M′ z2 O m2 R n2 , and the middle layer has a porous structure of the positive electrode active material, and the operation feasibility is high, and it is easy to control the raw material composition and structural parameters of each layer.
[0030] In some embodiments of the present application, the intermediate layer raw material includes an M″ source, where M″ includes a compound having at least one element of B, Al, or Si.
[0031] The third aspect of the present application provides a positive electrode plate, which includes: the positive electrode active material of the first aspect of the present application or the positive electrode active material prepared by the preparation method of the second aspect of the present application.
[0032] The fourth aspect of the present application provides a battery, which includes: the positive electrode plate of the third aspect of the present application.
[0033] The fifth aspect of the present application provides an electrical device, which includes: the battery of the fourth aspect of the present application.
[0034] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0036] Figure 1 Schematic diagram of a cross section of a secondary particle of a positive electrode active material according to one embodiment of the present application.
[0037] Figure 2 This is a scanning electron microscope image of a cross section of secondary particles of positive electrode active material in the active material layer of the positive electrode plate according to Example 1 of the present application.
[0038] Figure 3 It is a scanning electron microscope image of the cross section of the secondary particles of the positive electrode active material in the active material layer of the positive electrode sheet according to Comparative Example 2 of the present application.
[0039] Figure 4 It is a schematic structural diagram of a battery according to one embodiment of the present application.
[0040] Figure 5 It is a schematic structural diagram of a battery module according to one embodiment of the present application.
[0041] Figure 6 It is a schematic diagram of the structure of a battery pack according to one embodiment of the present application.
[0042] Figure 7 is an exploded view of a battery pack according to one embodiment of the present application.
[0043] Figure 8 It is a schematic diagram of an embodiment of an electric device using a battery as a power source according to an embodiment of the present application.
[0044] Description of reference numerals:
[0045] 11: inner core; 12: middle layer; 13: outer shell; 1: battery; 2: battery module; 3: battery pack; 4: upper case; 5: lower case. DETAILED DESCRIPTION
[0046] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.
[0047] Below, the embodiments of the positive electrode active material and its preparation method, positive electrode sheet, battery and electric device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0048] The "range" disclosed in the present application is defined in the form of a lower limit and / or an upper limit, and a given range is defined by selecting a lower limit and / or an upper limit, and the selected lower limit and / or upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end value, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form an unambiguous range, and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, each individually disclosed point or single value itself can be combined with any other point or single value as a lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that the range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following ranges are all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range "a-b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0049] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0050] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0051] If there is no special explanation, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps S1 and S2, which means that the method may include steps S1 and S2 performed sequentially, or may include steps S2 and S1 performed sequentially. For example, the method may also include step S3, which means that step S3 may be added to the method in any order. For example, the method may include steps S1, S2 and S3, or may include steps S1, S3 and S2, or may include steps S3, S1 and S2, etc.
[0052] If there is no special explanation, the "include" and "comprising" mentioned in this application represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0053] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0054] If there is no special explanation, in this application, the term "and / or" is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0055] In the present application, the terms "plurality" and "multiple" refer to two or more.
[0056] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions. Unless otherwise specified, the terms used in this application have the well-known meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).
[0057] With the continuous advancement of the green environmental protection theme, the application of lithium-ion batteries has penetrated into all aspects of life, including vehicles, electronic equipment, energy storage devices, etc. However, with the continuous promotion of battery applications, people's requirements for batteries are getting higher and higher. Among them, high-nickel layered positive electrode active materials generally undergo severe volume deformation during the cyclic charge and discharge process, which will cause a large amount of internal stress accumulation in the material. When the degree of internal stress accumulation in the material is too high, it will cause cracking inside the material. When the cracks extend to the surface of the positive electrode active material, the electrolyte will penetrate into the positive electrode active material in large quantities, affecting the material performance. At present, porous structures are mostly used to improve this problem, but in existing positive electrode active materials, the porous structure is usually evenly distributed inside the secondary particles of the material, and a large number of porous structures will aggravate the erosion of the electrolyte on the inside of the material, thereby affecting the material's cycle performance.
[0058] In the present application, by improving the structure of the positive electrode active material particles, the particles have a multilayer structure of a core, an intermediate layer and an outer shell layer from the inside to the outside, wherein the nickel-containing positive electrode active material located in the core is doped with M' elements (including at least one of Y, La, Mo, Zr, W, Sb, Nb, Te, Sr, Ti or Ga), which can improve the volume stability of the core positive electrode active material during the charge and discharge process and reduce the risk of cracking inside the positive electrode active material particles. At the same time, the intermediate layer is formed into a porous structure, and the intermediate layer can be used to accommodate the volume deformation and stress accumulation inside the positive electrode active material particles, thereby inhibiting the extension of cracks inside the positive electrode active material particles to the surface. Therefore, the volume stability of the positive electrode active material particles can be improved, and the risk of cracking during the charge and discharge cycle can be reduced, thereby improving the cycle performance.
[0059] The positive electrode active material disclosed in the embodiment of the present application is suitable for secondary batteries, and the battery disclosed in the embodiment of the present application can be used in electrical equipment using the battery as a power source or various energy storage systems using the battery as an energy storage element. Electrical equipment may include, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, and the like. Among them, electric toys may include fixed or mobile electric toys, for example, game consoles, electric car toys, electric ship toys, and electric airplane toys, and the like, and spacecraft may include airplanes, rockets, space shuttles, and spacecraft, and the like.
[0060] The first aspect of the present application provides a positive electrode active material, which comprises: a core, an intermediate layer and an outer shell layer, wherein the core comprises Li a1 Ni x1 M y1 M′ z1 O m1 R n1, 0.9 ≤ a1 ≤ 1.1, 0.6 ≤ x1 < 1, 0 ≤ y1 ≤ 0.4, 0 < z1 ≤ 0.01, 1.9 ≤ m1 ≤ 2.2, 0 ≤ n1 ≤ 0.1; M includes at least one element selected from Co, Mn, Al, Ta, Mg, Mo, Ga, Sn, Ge, Te, La, Ce; M' includes at least one element selected from Y, La, Mo, Zr, W, Sb, Nb, Te, Sr, Ti, or Ga; R includes at least one element selected from F, Cl, or S; The intermediate layer is coated on at least a part of the outer surface of the inner core, and the intermediate layer has a porous structure; The outer shell layer is coated on at least a part of the outer surface of the intermediate layer, and the outer shell layer includes Li a2 Ni x2 M y2 M′ z2 O m2 R n2 , 0.9 ≤ a2 ≤ 1.1, 0.6 ≤ x2 < 1, 0 ≤ y2 ≤ 0.4, 0 ≤ z2 ≤ 0.01, 1.9 ≤ m2 ≤ 2.2, 0 ≤ n2 ≤ 0.1.
[0061] For example, the values of a1 and a2 can be independently 0.9, 0.95, 1, 1.05, 1.1, etc., respectively, or can be any range composed of the above values; the values of x1 and x2 can be independently 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, etc., respectively, or can be any range composed of the above values; the values of y1 and y2 can be independently 0, 0.02, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, 0.22, 0.25, 0.28, 0.3, 0.32, 0.35, 0.38, 0.4, etc., respectively, or can be any range composed of the above values; the values of z1 and z2 can be independently 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, etc., respectively, or can be any range composed of the above values; the values of m1 and m2 can be independently 1.9, 1.92, 1.95, 1.98, 2, 2.02, 2.05, 2.08, 2.1, 2.12, 2.15, 2.18, 2.2, etc., respectively, or can be any range composed of the above values; the values of n1 and n2 can be independently 0, 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, etc., respectively, or can be any range composed of the above values. Optionally, x1 + y1 + z1 = 1; and / or, x2 + y2 + z2 = 1. The values of x1, x2, y1, y2, z1, and z2 satisfy the given range requirements, which is beneficial to obtaining a higher specific capacity and also beneficial to obtaining better cycling performance.
[0062] refer to Figure 1 It is understood that the positive electrode active material includes a core 11, an intermediate layer 12 and an outer shell layer 13, wherein the core 11 includes Li a1 Ni x1 M y1 M′ z1 O m1 R n1 , z1>0, the middle layer 12 is coated on at least a part of the outer surface of the core 11, and the outer shell 13 is coated on at least a part of the outer surface of the middle layer 12, and the outer shell includes Li a2 Ni x2 M y2 M′ z2 O m2 R n2 , z2≥0, that is, the nickel-containing positive electrode active material in the outer shell layer may be doped with M' element or may not be doped with M' element; the intermediate layer 12 is a porous structure. Among them, by doping the nickel-containing positive electrode active material located in the inner core 11, it is beneficial to improve the volume stability of the inner core of the positive electrode active material during the charge and discharge process, and reduce the risk of cracking inside the positive electrode active material particles. Among them, the doped M' element usually does not participate in the electrochemical reaction during the charge and discharge cycle, and can bind the unstable oxygen structure skeleton caused by the valence change of the Ni element during the charge and discharge process through a strong M'-O bonding effect, thereby improving the stability of the layered structure inside the material, reducing the risk of irreversible phase change of the positive electrode active material during the cycle, and inhibiting the collapse of the porous structure of the positive electrode active material in the late cycle; at the same time, by arranging an intermediate layer 12 with a porous structure between the inner core 11 and the outer shell layer 13, the intermediate layer can also obtain a larger porosity, which is beneficial to buffer the volume deformation and stress accumulation of the inner core, inhibit the cracking inside the positive electrode active material particles and the extension of the cracks to the surface, thereby inhibiting the cracking of the positive electrode active material during the cycle, and will not cause excessive electrolyte penetration, thereby improving the cycle performance of the positive electrode active material. It is understood that in the present application, the porous structure of the middle layer 12 is relative to the core 11 and the outer shell 13, and the porosity of the middle layer 12 is generally greater than that of the core 11 and the outer shell 13. For example, as a specific example, Figure 2 The cross-sectional view of the secondary particles of the positive electrode active material observed under a scanning electron microscope after the positive electrode sheet made of the positive electrode active material of one embodiment of the present application was cut by ion beam sputtering is shown. It can be clearly seen from the figure that compared with the inner core 11 and the outer shell 13, the middle layer 12 has an obvious porous structure.
[0063] Among them, in the actual operation process, the positive electrode active material can be cut (such as a single positive electrode active material can be cut by an ion beam sputtering method, or a positive electrode sheet can be prepared by using the positive electrode active material first, and then the positive electrode sheet can be cut) to obtain a cross section of the positive electrode active material, and the cross-sectional microscopic morphology of the positive electrode active material can be characterized by combining a scanning electron microscope (which can include but is not limited to a field emission scanning electron microscope FESEM, etc.) and / or a transmission electron microscope (which can include but is not limited to a high-resolution transmission electron microscope HRTEM), etc., to characterize the porous structure of the intermediate layer; in addition, the crystal structure of the positive electrode active material can be tested by XRD, and the type and content of the micro-region component elements in the cross-sectional area of the positive electrode active material can be analyzed by combining an energy dispersive spectrometer (EDS) and / or ICP (Inductively Coupled Plasma) element analysis to determine the elemental composition and ratio of the core and shell layers. It should be noted that the method of cutting the positive electrode active material is not particularly limited, and those skilled in the art can flexibly select according to actual needs.
[0064] The positive electrode active material of the present application has the following beneficial effects: by doping the M' element in the positive electrode active material located in the inner core, it is beneficial to improve the volume stability of the inner core of the positive electrode active material during the charge and discharge process, and reduce the risk of cracking inside the positive electrode active material particles; at the same time, by arranging a loose and porous intermediate layer between the inner core and the outer shell layer, it is also beneficial to buffer the volume deformation and stress accumulation of the inner core, and inhibit the cracking inside the positive electrode active material particles and the extension of the cracks to the surface. In this way, the risk of cracking of the positive electrode active material particles during the charge and discharge cycle can be reduced, and its volume stability and cycle performance can be improved.
[0065] It should be noted that Li a1 Ni x1 M y1 M′ z1 O m1 R n1 In the formula, M, M', and R may independently include one or more elements. Unless otherwise specified, when one or more of M, M', and R include more than two elements, the numerical range of the corresponding stoichiometric number in the chemical formula is limited not only to the stoichiometric number of each element as the site, but also to the sum of the stoichiometric numbers of each element as the site. For example, taking M' as an example, when M' is more than two elements M'1, M'2...M' n When M′1, M′2, ..., M′ n The respective stoichiometric numbers z11, z12, ... z1 n Each of them must fall within the numerical range of z1 specified in this application, and z11, z12...z1 nThe sum of M and R also needs to fall within this numerical range. Similarly, when M and R are two or more elements, the numerical range of the stoichiometric numbers of M and R in this application also has the above meaning. a2 Ni x2 M y2 M′ z2 O m2 R n2 In the above, M, M' and R may also independently include one or more elements. When M, M' and R are two or more elements, the numerical range of the stoichiometric numbers of M, M' and R also has the above meaning.
[0066] In addition, the kernel may include but is not limited to Li a1 Ni x1 M y1 M′ z1 O m1 R n1 The outer shell may include but is not limited to Li a2 Ni x2 M y2 M′ z2 O m2 R n2 For example, taking the kernel as an example, the kernel may only include Li a1 Ni x1 M y1 M′ z1 O m1 R n1 , and can also include Li a1 Ni x1 M y1 M′ z1 O m1 R n1 and other types of positive electrode active materials; wherein the specific types of other types of positive electrode active materials are not particularly limited, and those skilled in the art can flexibly select them according to actual needs, and will not be described in detail here. a1 Ni x1 M y1 M′ z1 O m1 R n1 It can include one or more of all positive electrode active materials that satisfy the general formula, Li a2 Ni x2 M y2 M′ z2 O m2 R n2It may also include one or more of all positive electrode active materials that satisfy the general formula. In addition, the composition of the core and the outer shell layer may be the same or different. Optionally, the composition of the core and the outer shell layer is the same. Optionally, the core may only include Li a1 Ni x1 M y1 M′ z1 O m1 R n1 , the outer shell can consist only of Li a2 Ni x2 M y2 M′ z2 O m2 R n2 .
[0067] It should be noted that in the positive electrode sheet, battery or electrical device, lithium ions will be consumed as the battery undergoes processes such as formation and circulation, so the measured lithium content a1 and / or a2 in the positive electrode active material will be less than 1; in addition, if the positive electrode sheet and the negative electrode sheet use a lithium supplement, the battery will undergo processes such as formation and circulation, and the measured lithium content a1 and / or a2 in the positive electrode active material will be greater than 1. In addition, the battery will be accompanied by lithium deintercalation and consumption during the charging and discharging process, and the molar content of lithium is different when the battery is discharged to different states. In the enumeration of positive electrode active materials in this application, the molar content of lithium is the initial state of the material, that is, the state before feeding. The positive electrode active material is applied to the battery system, and the molar content of lithium will change after the charge and discharge cycle. In addition, during the preparation process of the positive electrode active material, due to different control of the process such as oxygen content or factors such as lattice oxygen release, the oxygen content in the positive electrode active material will also be different. In the enumeration of positive electrode active materials in this application, the molar content of oxygen is only a theoretical state value, and the actual molar content of oxygen will fluctuate.
[0068] Furthermore, the positive electrode active material of the first aspect of the present application can further control the composition of the intermediate layer and the outer shell layer, the type of the positive electrode active material, the relative position relationship of each layer, the volume particle size distribution relationship, etc. on the basis of satisfying the above conditions to further optimize the performance of the positive electrode active material. That is, on the basis of satisfying the above conditions, one or more of the following conditions can also be optionally satisfied.
[0069] In some embodiments of the present application, the middle layer 12 may include: M″ p O q , 1≤p≤2, 2≤q≤3, M″ may include at least one element of B, Al or Si.
[0070] For example, the value of p can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, etc., or can be a range consisting of any of the above values. The value of q can be 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3, etc., or can be a range consisting of any of the above values. For another example, the intermediate layer can include one or more of Al2O3, B2O3, and SiO2. Using M″ p O q As an intermediate layer material, on the one hand, it is beneficial to reduce the risk that the intermediate layer material may have an adverse effect on the electrochemical properties of the positive electrode active material. On the other hand, in the actual preparation process, the given M″ element or the compound of the given M″ element can also be used to form a unique cross-linked structure (such as gel, etc.) in an alkaline environment. After sintering, a loose and porous skeleton structure can be obtained, which is beneficial for making the intermediate layer have a larger porosity and can also obtain a certain support strength. For example, a mixed solution can be obtained by mixing a core raw material including a nickel source, an M source, and an M′ source, and the mixed solution is subjected to a co-precipitation reaction to obtain a first particle; a solution formed by an intermediate layer raw material (such as an aluminum source, a silicon source, a boron source, etc.) is mixed with the first particle to undergo a precipitation reaction to obtain a second particle. At this time, the intermediate layer raw material can include M″ and / or M″ compounds, the precipitation reaction can be carried out in an alkaline environment, and the precipitation product with M″ elements in the precipitation process can form a unique cross-linked structure layer on the surface of the first particle; a solution formed by a shell layer raw material including a nickel source and an M source (optionally, the shell layer raw material can have the same composition as the core raw material) is mixed with the second particle to carry out a precipitation reaction to obtain a precursor particle; the precursor particle is mixed with a lithium source and then sintered to obtain a positive electrode active material. Among them, the positive electrode active material can be cut, and the intermediate layer area in the cross section of the positive electrode active material can be determined by using a scanning electron microscope and / or a transmission electron microscope, and the types of micro-region component elements in the cross section of the positive electrode active material are analyzed in combination with XRD testing and / or an energy dispersive spectrometer (EDS) to determine whether the intermediate layer contains M″ p O q . Optionally, M″ includes Al.
[0071] By making the intermediate layer meet the given conditions, on the one hand, it is helpful to reduce the risk that the intermediate layer material may have an adverse effect on the electrochemical properties of the positive electrode active material, and on the other hand, it is also beneficial to combine M″ p O q The formation method forms an intermediate layer with a porous structure in the positive electrode active material, which is beneficial to taking into account both the electrochemical performance and cycle stability of the positive electrode active material.
[0072] In some embodiments of the present application, in the positive electrode active material, the ratio of the molar number of the M″ element to the molar number of the Li element may be (0.005-0.02):(0.9-1.1), and may be (0.008-0.012):(0.9-1.1).
[0073] For example, in the positive electrode active material, the ratio of the molar number of the M″ element to the molar number of the Li element can be 0.005 / 1.1, 0.005 / 1.05, 0.005 / 1, 0.005 / 0.95, 0.005 / 0.9, 0.008 / 1.1, 0.008 / 1.05, 0.008 / 1, 0.008 / 0.95, 0.008 / 0.9, 0.01 / 1.1, 0.01 / 1.05, 0.01 / 1, 0.01 / 0.95, 0.01 / 0.9, 0.01 / 0.9 .012 / 1.1, 0.012 / 1.05, 0.012 / 1, 0.012 / 0.95, 0.012 / 0.9, 0.015 / 1.1, 0.015 / 1.05, 0.015 / 1, 0.015 / 0.95, 0.015 / 0.9, 0.02 / 1.1, 0.02 / 1.05, 0.02 / 1, 0.02 / 0.95, 0.02 / 0.9, etc., or can be a range consisting of any of the above values. Optionally, the types of M″ and M′ elements are different. ICP elemental analysis can be used to determine the content of M″ element and Li element in the positive electrode active material, and then obtain the ratio of the total molar number of the two. M″ in the intermediate layer p O q The content can be indirectly described by the content of the M″ element. Increasing the content of the M″ element is beneficial to increasing the thickness of the intermediate layer. Making the content of the M″ element meet the given conditions is beneficial to making the intermediate layer have a suitable thickness, improving the buffering capacity of the intermediate layer to the volume expansion and stress accumulation of the inner core, and reducing the risk of cracking of the positive electrode active material particles. At the same time, it is also beneficial to reduce the impact on the volume energy density of the positive electrode active material, and is beneficial to further take into account the high specific capacity and cycle stability of the positive electrode active material. Optionally, in the positive electrode active material, the ratio of the molar number of the M″ element to the molar number of Li can be (0.008~0.012): (0.9~1.1). Meeting this condition is beneficial to further reduce the possible negative impact on the volume energy density of the positive electrode active material.
[0074] Controlling the relative amounts of the M″ element and the Li element to meet the given range is beneficial to further taking into account the high specific capacity and cycle stability of the positive electrode active material.
[0075] In some embodiments of the present application, z2>0.
[0076] In the positive electrode active material, by doping the positive electrode active material in the outer shell layer with the M' element, the cycle stability of the outer shell layer can be further improved, which is not only conducive to reducing the risk of cracking of the outer shell layer itself, but also further conducive to inhibiting the extension of cracks inside the positive electrode active material particles to the surface, and improving its volume stability and cycle performance. Among them, EDS energy spectrum analysis can be used to determine the type and content of the micro-region component elements in the outer shell layer, and / or combined with XRD to test the crystal structure of the positive electrode active material. Optionally, the intermediate layer may include the M' element or may not include the M' element.
[0077] By making the outer shell layer meet the given conditions, it is beneficial to further improve the cycle stability of the positive electrode active material.
[0078] In some embodiments of the present application, the core 11 may include Li a1 Ni x1 Co y11 Mn y12 M′ z1 O m1 R n1 , 0≤y11≤0.2, 0≤y12≤0.2, y11 and y12 are not 0 at the same time; and / or, the outer shell layer 13 may include: Li a2 Ni x2 Co y21 Mn y22 M′ z2 O m2 R n2 , 0≤y21≤0.2, 0≤y22≤0.2, y21 and y22 are not 0 at the same time.
[0079] It is understood that the core can be either a single material or a plurality of materials satisfying the general formula Li a1 Ni x1 M y1 M′ z1 O m1 R n1 Similarly, the outer shell layer can be a single material or a mixture of multiple materials satisfying the general formula Li a2 Ni x2 M y2 M′ z2 O m2 R n2 For example, taking the core as an example, the core may include but is not limited to Li a1 Ni x1 Co y11 Mn y12 M′ z1 O m1 R n1 , Lia1 Ni x1 Co y11 M′ z1 O m1 R n1 , Li a1 Ni x1 Mn y12 M′ z1 O m1 R n1 As a specific example, the kernel may include Li a1 Ni x1 Co y11 Mn y12 M′ z1 O m1 R n1 As another specific example, the outer shell layer may include: Li a2 Ni x2 Co y21 Mn y22 M′ z2 O m2 R n2 Among them, Li a1 Ni x1 Co y11 Mn y12 M′ z1 O m1 R n1 It can be a single material or a mixture of multiple positive electrode active materials satisfying the general formula; Li a2 Ni x2 Co y21 Mn y22 M′ z2 O m2 R n2 It may be a single material or a mixture of a plurality of positive electrode active materials satisfying the general formula.
[0080] The values of y11 and y12 can be independently 0, 0.02, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, etc., or can be a range consisting of any of the above values; the values of y21 and y22 can be independently 0, 0.02, 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, etc., or can be a range consisting of any of the above values. Co addition to Ni-containing layered positive electrode active materials is beneficial to stabilizing the layered structure, inhibiting lithium-nickel mixing, and improving the cycle performance of the positive electrode active material. Manganese addition is beneficial to improving structural stability and thermal stability. The values of x1, x2, y11, y12, y21, and y22 meet the given range, which is beneficial to obtaining a higher specific capacity and better cycle performance and coulombic efficiency. The crystal structure of the positive electrode active material can be tested in combination with XRD, and the positive electrode active material can be cut and combined with EDS energy spectrum analysis and / or ICP element analysis to analyze the types and contents of micro-region component elements in the cross-sectional area of the positive electrode active material.
[0081] Making the composition of the core and / or shell layer satisfy the given range conditions is beneficial to taking into account both the high specific capacity and the cycle performance of the lithium battery.
[0082] In some embodiments of the present application, 0.002≤z1≤0.008; and / or, 0.002≤z2≤0.008.
[0083] For example, the values of z1 and z2 can be independently 0, 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01, etc., or can be a range composed of any of the above values. As mentioned above, the values of z1 and z2 can be measured in combination with ICP elemental analysis and / or EDS analysis. For example, when the composition of the materials in the core and the outer shell layer is the same, the values of z1 and z2 are the same, and the values of z1 and z2 can be directly obtained by performing ICP elemental analysis on the positive electrode active material particles. As the values of z1 and z2 increase, the doping amount of M' in the positive electrode active material located in the core and the outer shell layer also increases, which is beneficial to further improve the volume stability of the positive electrode active material during the cycle and reduce the risk of cracking. In addition, controlling the values of z1 and z2 to independently satisfy the given ranges is also beneficial to reducing the risk of significantly increasing the impurity phase due to excessive M′ doping, thereby affecting the electrochemical performance of the positive electrode active material.
[0084] Controlling the values of z1 and / or z2 to meet the given range conditions is beneficial to improving the cycle stability of the positive electrode active material and reducing the risk of degradation of the electrochemical performance of the positive electrode active material.
[0085] In some embodiments of the present application, the particle size of the positive electrode active material is D1, the distance from the inner surface of the intermediate layer 12 to the center of the core 11 is greater than or equal to 0.3D1, and the distance from the outer surface of the intermediate layer 12 to the center of the core 11 is less than or equal to 0.4D1.
[0086] For example, the distance from the inner surface of the middle layer to the center of the inner core can be 0.3D1, 0.305D1, 0.31D1, 0.315D1, 0.32D1, 0.325, 0.33D1, 0.335D1, 0.34D1, 0.345D1, 0.35D1, 0.355D1, 0.36D1, 0.37D1, 0.375D1, 0.38D1, 0.385D1, 0.39D1, 0.395D1, etc., or it can be a range composed of any of the above values. The distance from the outer surface of the middle layer to the center of the inner core can be 0.4D1, 0.395D1, 0.39D1, 0.385D1, 0.38D1, 0.375D1, 0.37D1, 0.365D1, 0.36D1, 0.355D1, 0.35D1, 0.345D1, 0.34D1, 0.335D1, 0.33D1, 0.325, 0.32D1, 0.315D1, 0.31D1, 0.305D1, etc., or can be a range composed of any of the above values. It can be understood that the distance from the outer surface of the intermediate layer to the center of the core is greater than the distance from the inner surface of the intermediate layer to the center of the core, the distance from the outer surface of the intermediate layer to the center of the core and the distance from the inner surface of the intermediate layer to the center of the core can be understood as the average distance, the distance from the inner surface of the intermediate layer to the center of the core can be understood as the particle size of the core, and the distance from the outer surface of the intermediate layer to the center of the core and the distance from the inner surface of the intermediate layer to the center of the core can be understood as the thickness of the intermediate layer. Among them, the particle size of the positive electrode active material can be understood as the absolute particle size of a single positive electrode active material particle or the volume distribution particle size D of the positive electrode active material particle. v 50,D v50 refers to the particle size corresponding to the cumulative volume distribution percentage reaching 50% (i.e., the volume content of particles less than or equal to this particle size and the volume content of particles greater than or equal to this particle size each account for 50% of the total particle volume). It can be measured with reference to the standard GB / T19077-2016 / ISO 13320:2009 using a laser particle size analyzer (Malvern Master Size 2000). The particle size of the inner core also has the above meaning. The specific test process may include: taking an appropriate amount of the sample to be tested (the sample concentration is sufficient to ensure a light shielding degree of 8%-12%), adding 20ml of deionized water, and ultrasonicating for 5min (53KHz / 120W) to ensure that the sample is completely dispersed, and then measuring the sample according to the GB / T19077-2016 / ISO 13320:2009 standard. The distance from the middle layer to the center of the inner core can be estimated by cutting the positive active material and combining it with a scanning electron microscope or a transmission electron microscope. By controlling the distance from the inner surface and outer surface of the intermediate layer to the center of the inner core to meet the given conditions, on the one hand, the high porosity structure of the intermediate layer can be used to inhibit the internal cracking of the positive electrode active material and the extension of the cracks to the outer surface. On the other hand, it is beneficial to increase the buffering capacity of the intermediate layer to the volume deformation and stress accumulation of the inner core, and improve the inhibitory effect of the intermediate layer on the cracking of the positive electrode active material. At the same time, it is also beneficial to reduce the risk of the intermediate layer cracks extending quickly to the outer surface due to the intermediate layer being too close to the outer shell layer, or the risk of the outer shell layer porosity being too large due to the intermediate layer directly extending to the outer shell layer, thereby causing a large amount of electrolyte to penetrate into the material and affect the material performance; in addition, it can also reduce the risk of the ion migration rate and volume energy density of the positive electrode active material being affected by the excessive thickness of the intermediate layer.
[0087] Controlling the distance from the middle layer of the positive electrode active material to the center of the inner core to meet the given conditions is not only beneficial to improving the cracking risk of the positive electrode active material during the cycle process, but also beneficial to reducing the negative impact on the ion migration rate and volume energy density, and is beneficial to further taking into account the cycle performance, rate performance and energy density of the positive electrode active material.
[0088] In some embodiments of the present application, the particle size of the positive electrode active material is D1, and the thickness of the intermediate layer 12 may be 0.05D1 to 0.0625D1.
[0089] For example, the thickness of the intermediate layer 12 can be 0.05D1, 0.0525D1, 0.055D1, 0.0575D1, 0.06D1, 0.0625D1, etc., or can be a range composed of any of the above values. The thickness of the intermediate layer can be obtained by cutting the positive electrode active material and estimating it in combination with a scanning electron microscope or a transmission electron microscope. Among them, in the present application, the thickness of the intermediate layer can be understood as the average thickness of the intermediate layer of the positive electrode active material particles. Controlling the thickness of the intermediate layer to meet the given conditions can not only make the intermediate layer have an effective buffering capacity for the volume deformation and stress accumulation of the inner core, but also help to inhibit the cracking of the positive electrode active material and the outward extension of the cracks, and at the same time, it can further reduce the negative impact of the thickness of the intermediate layer on the ion migration rate and volume energy density of the positive electrode active material.
[0090] Controlling the thickness of the intermediate layer to meet the given conditions is beneficial not only to improving the cracking risk of the positive electrode active material during the cycle process, but also to further reduce the negative impact on the ion migration rate and volume energy density, and is beneficial to further taking into account the cycle performance, rate performance and energy density of the positive electrode active material.
[0091] In some embodiments of the present application, in the cut surface of the positive electrode active material through the center of its core, the cross-sectional particle size is 0.9 to 1.1 times the volume average particle size Dv50 of the positive electrode active material, and the cross-sectional area of the intermediate layer 12 can be 5% to 20% of the total cross-sectional area of the positive electrode active material. For example, the cross-sectional area of the intermediate layer 12 can be 5%, 8%, 10%, 12%, 15%, 18%, 20%, etc. of the total cross-sectional area of the positive electrode active material, or can be a range composed of any of the above values. Controlling the cross-sectional area of the intermediate layer to meet the given conditions is also conducive to improving the cracking risk of the positive electrode active material during the cycle process, and is conducive to reducing the negative impact on the ion migration rate and volume energy density, thereby further balancing the cycle performance, rate performance and energy density of the positive electrode active material.
[0092] In some embodiments of the present application, the volume particle size distribution of the positive electrode active material satisfies:
[0093] For example, The value of can be 1.1, 1.2, 1.3, 1.5, 1.8, 2, 2.2, 2.5, 3, 3.5, 4, etc., any value greater than or equal to 1.1, or can be a range consisting of any of the above values. Optionally, The value can be greater than or equal to 1.2. Among them, the volume particle size Dv90 and Dv10 of the positive electrode active material can also refer to the standard GB / T19077-2016 / ISO 13320:2009, and be measured using a laser particle size analyzer (Malvern Master Size 2000). Dv10 refers to the particle size corresponding to when the cumulative volume distribution percentage reaches 10%, that is, the volume content of particles less than or equal to this particle size accounts for 10% of the total particle volume; Dv90 refers to the particle size corresponding to when the cumulative volume distribution percentage reaches 90%, that is, the volume content of particles less than or equal to this particle size accounts for 90% of the total particle volume. The particle size distribution of the positive electrode active material particles that meets the given conditions is wider, which is conducive to obtaining a higher compaction density, and thus is conducive to improving the volume energy density of the battery. Optionally, Meeting the given conditions is conducive to further improving the volume energy density of the battery.
[0094] Controlling the volume particle size distribution of the positive electrode active material to meet the given conditions is beneficial to improving the volume energy density of the battery.
[0095] In some embodiments of the present application, the volume average particle size Dv50 of the positive electrode active material may be 6 μm to 18 μm.
[0096] For example, the volume average particle size Dv50 of the positive electrode active material can be 6μm, 8μm, 10μm, 12μm, 14μm, 16μm, 18μm, etc., or can be a range composed of any of the above values, and can be selected as 8μm to 12μm. Making the volume average particle size Dv50 of the positive electrode active material meet the given conditions is beneficial to improving the stability of the overall structure of the positive electrode active material particles, and is also beneficial to making the positive electrode active material have the advantages of a small internal conduction distance and few surface side reactions, thereby further improving the electrochemical performance of the positive electrode active material.
[0097] In some embodiments of the present application, the compaction density of the positive electrode active material under a pressure of 5 tons may be greater than or equal to 3.4 g / cm 3 For example, the compaction density of the positive electrode active material under 5 tons of pressure can be 3.4 g / cm 3 、3.45g / cm 3 、3.5g / cm 3 、3.55g / cm 3 、3.6g / cm 3 、3.65g / cm 3 、3.7g / cm 3 、3.75g / cm 3 、3.8g / cm 3 、3.85g / cm 3etc., or can be a range composed of any of the above values. The tap density of the positive electrode active material can be tested with reference to the national standard GB / T 24533-2009. Controlling the tap density of the positive electrode active material to meet the given conditions is beneficial to further improving the volumetric energy density of the battery.
[0098] Currently, there is a solution for preparing a positive electrode active material with a porous structure by embedding an organic template in a precursor and combining high-temperature sintering. However, due to the dispersibility of the organic matter, it is difficult to control the position and distribution of the porous structure, and the preparation of the precursor requires the hydrothermal method, which is cumbersome and expensive and difficult to carry out large-scale industrial production.
[0099] In view of this, based on the same inventive concept as the positive electrode active material in the first aspect of the present application, the second aspect of the present application provides a method for preparing a positive electrode active material, which includes:
[0100] Mixing the core raw materials including a nickel source, an M source, and an M' source to obtain a mixed solution, and performing a first precipitation reaction on the obtained mixed solution to obtain first particles; mixing the solution formed by the intermediate layer raw materials with the first particles to perform a second precipitation reaction to obtain second particles; mixing the shell layer raw materials including a nickel source and an M source, and mixing the obtained mixed solution with the second particles to perform a third precipitation reaction to obtain precursor particles; mixing the precursor particles with a lithium source and performing sintering to obtain a positive electrode active material; wherein: the precipitation product formed on the outer surface of the first particles during the second precipitation reaction forms a porous structure through sintering; the positive electrode active material includes: a core, an intermediate layer, and a shell layer, and the core includes Li a1 Ni x1 M y1 M′ z1 O m1 R n1 , 0.9 ≤ a1 ≤ 1.1, 0.6 ≤ x1 < 1, 0 ≤ y1 ≤ 0.4, 0 < z1 ≤ 0.01, 1.9 ≤ m1 ≤ 2.2, 0 ≤ n1 ≤ 0.1; M includes at least one element of Co, Mn, Al, Ta, Mg, Mo, Ga, Sn, Ge, Te, La, Ce; M' includes at least one element of Y, La, Mo, Zr, W, Sb, Nb, Te, Sr, Ti or Ga; R includes at least one element of F, Cl or S; the intermediate layer covers at least a part of the outer surface of the core, and the intermediate layer has a porous structure; the shell layer covers at least a part of the outer surface of the intermediate layer, and the shell layer includes Li a2 Ni x2 M y2 M′ z2 O m2 R n2, 0.9≤a2≤1.1, 0.6≤x2<1, 0≤y2≤0.4, 0≤z2≤0.01, 1.9≤m2≤2.2, 0≤n2≤0.1.
[0101] The method for preparing positive electrode active materials in the present application has the following beneficial effects: not only can the core including Li a1 Ni x1 M y1 M′ z1 O m1 R n1 , the outer shell includes Li a2 Ni x2 M y2 M′ z2 O m2 R n2 , and the middle layer has a positive electrode active material with a porous structure, and the operation feasibility is high, and it is easy to control the raw material composition of each layer and the structural parameters such as the position, thickness, and pore structure of the middle layer. It should be noted that the preparation method of the second aspect of the present application and the positive electrode active material of the first aspect of the present application are based on the same inventive concept, and the characteristics and effects described for the positive electrode active material of the first aspect of the present application are also applicable to the preparation method of the second aspect of the present application, which will not be repeated here.
[0102] In some embodiments of the present application, when preparing the first particle, the Li a1 Ni x1 M y1 M′ z1 O m1 R n1 The core raw materials including the nickel source, the M source, and the M′ source are mixed to obtain a mixed solution in a stoichiometric ratio; when preparing the precursor particles, the Li a2 Ni x2 M y2 M′ z2 O m2 R n2 The shell layer raw materials including the nickel source and the M source are mixed in a stoichiometric ratio to obtain a mixed solution; as some further specific examples, x1+y1+z1=1; and / or, x2+y2+z2=1.
[0103] In some embodiments of the present application, the intermediate layer raw material may include an M″ source, and M″ may include a compound having at least one element of B, Al, or Si. Optionally, the compound of M″ may include an oxide and / or a salt.
[0104] In some embodiments of the present application, the shell layer raw material and the core raw material may be the same or different. For example, the types and proportions of the shell layer raw material and the core raw material may be exactly the same. For another example, the difference between the shell layer raw material and the core raw material may only be that the shell layer raw material does not contain the M′ source.
[0105] In some embodiments of the present application, the first precipitation reaction and the third precipitation reaction are coprecipitation reactions, and the second precipitation reaction can be a gelation precipitation reaction. The first precipitation reaction, the second precipitation reaction, and the third precipitation reaction can each independently select whether to add a precipitant and / or a complexing agent.
[0106] In some embodiments of the present application, taking the nickel-cobalt-manganese layered positive electrode active material used in lithium batteries as an example, the nickel source, manganese source, cobalt source, and M′ source can be mixed according to a preset stoichiometric ratio to obtain a mixed solution, and a portion of the mixed solution is subjected to a coprecipitation reaction to prepare first particles. When the first particles grow to a first preset particle size, the first particles are mixed with a solution formed using an M″ source to perform a precipitation reaction to prepare second particles, wherein the solution formed using the M″ source can be obtained by mixing an oxide of the M″ element with an acidic or alkaline solution, or by dissolving an M″ salt in an aqueous solvent. When the second particles grow to a second preset particle size, the second particles are mixed with the remaining mixed solution and subjected to a coprecipitation reaction to prepare precursor particles. When the precursor particle size grows to a third preset particle size, the precursor particles are mixed with a lithium salt according to a preset ratio and sintered to obtain a positive electrode active material. Optionally, in each precipitation reaction, it is possible to independently select whether to add a precipitant and / or a complexing agent.
[0107] It can be understood that in the present application, the specific types of raw material components such as nickel source, M′ source, M″ source and lithium source are not particularly limited, and those skilled in the art can flexibly choose according to actual needs. For example, M′ source may include but is not limited to one or more of sulfates, carbonates, nitrates, chlorides, silicates, acetates, oxalates, oxides, hydroxides, etc.; M″ source may include but is not limited to one or more of sulfates, nitrates, chlorides, fluorides, oxalates, acetates, etc.; lithium source may include but is not limited to one or more of LiOH·H2O, Li2CO3, Li2SO4, LiNO3, LiC2O4, CH3COOLi, etc.; other raw material components such as nickel source (such as cobalt source or manganese source, etc.) may also independently include but are not limited to one or more of sulfates, nitrates, carbonates, chlorides, fluorides, oxalates, acetates, etc. In addition, in the first precipitation reaction, the second precipitation reaction and the third precipitation reaction, as well as in operations such as sintering, the controlled process parameters (such as pH value, reaction time, reaction temperature, heating rate, sintering atmosphere, etc.) are not particularly limited, and those skilled in the art can flexibly select according to actual needs. For example, the temperature of each precipitation reaction can be independently 40°C to 80°C, and the pH value can be 11 to 14, or 12 to 13; the sintering temperature can be 600°C to 850°C, or 650 to 750°C, the sintering time can be 8h to 18h, or 10 to 15h, the heating rate can be 0.5°C / min to 5°C / min, or 1°C / min to 3°C / min, and the sintering atmosphere can be air atmosphere, oxygen atmosphere, a mixed atmosphere of oxygen and nitrogen or inert gas, and the like. In addition, in the present application, the specific types of precipitants and complexing agents are not particularly limited, and those skilled in the art can flexibly select them according to actual needs. For example, the precipitant may include but is not limited to one or more of sodium hydroxide, sodium carbonate, potassium carbonate, and potassium hydroxide, and the complexing agent may include but is not limited to one or more of ammonia water, ammonium chloride, ammonium sulfate, urea, citric acid, EDTA, etc.
[0108] As some specific examples, for kernels including Li a1 Ni x1 Co y11 Mn y12 M′ z1 O m1 R n1 , the outer shell includes Li a2 Ni x2 Co y21 Mn y22 M′ z2 O m2 R n2 , the middle layer includes M″ p O qThe positive electrode active material, the preparation process of which may specifically include: mixing Ni salt, Co salt, Mn salt, and M' source according to a preset ratio to prepare a mixed solution, pumping the mixed solution, precipitant, and complexing agent into a reactor at a certain pump speed, controlling the pH and reaction temperature of the material in the reactor to perform a coprecipitation reaction, monitoring the particle size in the reactor (specifically, a small amount of product can be regularly discharged from the discharge port below the reactor to test the particle size. The reactor used for the reaction is usually large, and discharging a small amount of product has almost no effect on the reaction conditions and process). When the material particles in the reactor grow to 3 / 5 to 4 / 5 of the volume particle size Dv50 of the target particles (i.e., precursor particles), stop pumping the mixed salt solution, pump the solution formed by using the M" source into the reactor, and after the solution formed by the M" source is completely pumped in, pump the remaining mixed solution into the reactor for reaction, monitor the particle size in the reactor, and obtain precursor particles grown to the target particle volume particle size. The obtained precursor particles are mixed with a lithium source and sintered to obtain a positive electrode active material. Among them, the sintering temperature can be 600℃~850℃, optionally 650~750℃, the sintering time can be 8h~18h, optionally 10~15h, the heating rate can be 0.5℃ / min~5℃ / min, optionally 1℃ / min~3℃ / min, and the sintering atmosphere can be air atmosphere, oxygen atmosphere, a mixed atmosphere of oxygen and nitrogen or inert gas.
[0109] The third aspect of the present application provides a positive electrode plate, which includes: the positive electrode active material of the first aspect of the present application, or the positive electrode active material prepared by the method of the second aspect of the present application.
[0110] In a battery, a positive electrode sheet generally includes a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, wherein the positive electrode active material layer includes a positive electrode active material.
[0111] The positive electrode current collector may be a conventional metal foil or a composite current collector (a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the positive electrode current collector may include at least one of copper foil, aluminum foil, nickel foil, stainless steel foil, stainless steel mesh, and carbon-coated aluminum foil, and may be aluminum foil.
[0112] The positive electrode active material layer may also optionally include at least one of a binder, a conductive agent and other optional auxiliary agents. As an example, the conductive agent may include but is not limited to one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. As an example, the binder may include but is not limited to one or more of styrene-butadiene rubber (SBR), water-based acrylic resin, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-vinyl acetate copolymer (EVA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyvinyl butyral (PVB).
[0113] These materials are all commercially available.
[0114] The fourth aspect of the present application provides a battery, which includes: the positive electrode sheet of the third aspect of the present application. Thus, the battery can have good cycle stability and long service life.
[0115] A battery is a battery that can be used again by recharging the active materials after discharge.
[0116] It is understandable that the battery proposed in the present application is a lithium battery, such as a lithium-ion battery.
[0117] Generally, a battery includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the charge and discharge process of the battery, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet to play a role of isolation. The electrolyte plays a role of conducting ions between the positive electrode sheet and the negative electrode sheet.
[0118] [Negative electrode]
[0119] In a battery, the negative electrode plate generally includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, wherein the negative electrode active material layer includes a negative electrode active material. The negative electrode current collector may be a conventional metal foil or a composite current collector (for example, a metal material may be disposed on a polymer substrate to form a composite current collector). As an example, the negative electrode current collector may be a copper foil.
[0120] In some embodiments of the present application, the battery of the fourth aspect of the present application can be a lithium-ion battery. In this case, the specific type of the negative electrode active material is not limited. Active materials known in the art that can be used for the negative electrode of lithium-ion batteries can be used. Those skilled in the art can choose according to actual needs. As an example, the negative electrode active material may include but is not limited to at least one of lithium metal, carbon material, alloy material, silicon-based material, phosphorus-based material, etc. Specifically, the carbon material may include but is not limited to at least one of hard carbon, soft carbon, amorphous carbon, and nanostructured carbon material; the alloy material may include but is not limited to alloy materials formed by at least one of Si, Ge, Sn, Pb, and Sb; the silicon-based material may include but is not limited to silicon-carbon material, silicon dioxide, etc. These materials can all be obtained through commercial channels.
[0121] The negative electrode active material layer generally further optionally includes a binder and a conductive agent, the conductive agent is used to improve the conductivity of the negative electrode active material layer, and the binder is used to firmly bond the negative electrode active material and the conductive agent to the negative electrode current collector. The present application does not specifically limit the types of conductive agents and binders, and they can be selected according to actual needs. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. As an example, the binder may include at least one of styrene butadiene rubber (SBR), styrene-butadiene rubber (SBCs), water-based acrylic resin (water-based acrylic resin) and carboxymethyl cellulose (CMC).
[0122] The negative electrode active material layer may also optionally include a thickener, such as carboxymethyl cellulose (CMC). However, the present application is not limited thereto, and the present application may also use other materials that can be used as thickeners for negative electrode sheets of lithium-ion batteries.
[0123] In some embodiments of the present application, the battery of the fourth aspect of the present application may be a lithium metal battery, in which case the negative electrode active material may include but is not limited to metallic lithium. For example, the negative electrode active material may also be an alloy formed by metallic lithium and other various metals or non-metallic elements.
[0124] In some embodiments of the present application, the battery of the fourth aspect of the present application can also be a negative electrode-free lithium metal battery. In this case, the negative electrode is composed of only a metal foil current collector, and there is no lithium metal on its surface. During the cycle process, only the lithium in the positive electrode is used, and it is precipitated and peeled off in the form of lithium metal on the negative electrode side.
[0125] [Electrolyte]
[0126] The electrolyte may include an electrolyte salt and a solvent.
[0127] As an example, the electrolyte lithium salt may include but is not limited to at least one of lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium tetrafluoroborate, lithium bisoxalatoborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium trifluoromethylsulfonate and lithium bis(trifluoromethylsulfonyl)imide.
[0128] As an example, the solvent may include at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0129] In some embodiments, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature performance.
[0130] [Isolation film]
[0131] As the above-mentioned isolation membrane, the present application has no special restrictions and any known porous structure isolation membrane with electrochemical stability and mechanical stability can be selected according to actual needs. For example, it can include a single-layer or multi-layer film containing at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride.
[0132] The embodiment of the present application has no particular limitation on the shape of the battery, which can be cylindrical, square or any other shape. Figure 4 A square-structured battery 1 is shown as an example.
[0133] In some embodiments, the battery may include an outer packaging for packaging the positive electrode sheet, the negative electrode sheet, and the electrolyte.
[0134] In some embodiments, the outer package may include a shell and a cover plate. The shell may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell has an opening connected to the receiving cavity, and the cover plate can be covered on the opening to close the receiving cavity.
[0135] The positive electrode sheet, the negative electrode sheet and the separator can be wound or laminated to form an electrode assembly. The electrode assembly is packaged in the receiving cavity. The number of electrode assemblies contained in the battery can include one or more, which can be adjusted according to demand.
[0136] In some embodiments, the outer packaging of the battery may include a hard shell, such as a hard plastic shell, an aluminum shell, or a steel shell.
[0137] The outer packaging of the battery may also include a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0138] In some embodiments, the battery may be either a single battery cell or a battery module or battery pack assembled from battery cells. The battery module or battery pack may contain multiple batteries, and the specific number may be adjusted according to the application and capacity of the battery module.
[0139] Figure 5 2 is an example of a battery module 2. Figure 5 In the battery module 2, the multiple batteries 1 can be arranged in sequence along the length direction of the battery module 2. Of course, they can also be arranged in any other manner. Further, the multiple batteries 1 can be fixed by fasteners.
[0140] The battery module 2 may also include a housing having a storage space, in which a plurality of batteries 1 are stored. In some embodiments, the battery modules may be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0141] Figure 6 and Figure 7 The battery pack 3 is used as an example. Figure 6 and Figure 7 The battery pack 3 may include a battery box and a plurality of battery modules 2 disposed in the battery box. The battery box includes an upper box body 4 and a lower box body 5. The upper box body 4 can cover the lower box body 5 and form a closed space for accommodating the battery modules 2. The plurality of battery modules 2 can be arranged in the battery box in any manner.
[0142] The fifth aspect of the present application provides an electrical device, which includes: the battery of the fourth aspect of the present application.
[0143] Specifically, the battery can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks), electric trains, ships, satellites, and energy storage systems.
[0144] Figure 8 As an example of an electric device, the electric device includes a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. As another example, the electric device may include a mobile phone, a tablet computer, and a laptop computer. The electric device is usually required to be thin and light, and a battery may be used as a power source.
[0145] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0146] Example 1
[0147] (I) Preparation of positive electrode active materials
[0148] S1: LiNi based 0.928 Mn 0.07 Zr 0.002 O2 in a stoichiometric ratio, nickel sulfate, manganese sulfate, and zirconium sulfate are mixed according to a molar ratio of 0.928:0.07:0.002 for nickel element in nickel sulfate, manganese element in manganese sulfate, and zirconium element in zirconium sulfate; a mixed salt solution is prepared, sodium hydroxide solution is used as a precipitant, and ammonia water is used as a complexing agent, pure water and precipitant are supplied to the reactor, stirring is started, a constant temperature of 60°C is maintained, stirring is started, and the mixed liquid solution, precipitant solution, and complexing agent solution are supplied to the reactor for co-precipitation reaction During this period, the concentration and pH of the ammonia water in the reactor were controlled to be constant, and a small amount of reaction products were discharged from the bottom of the reactor periodically to test the Dv50 particle size to monitor the particle size change of the material particles inside the reactor. The volume particle size Dv50 of the precursor particles to be obtained was designed to be 12 μm. When the particle size of the material particles in the reactor reached 3 / 5 of the Dv50 particle size, i.e., 7.2 μm, the supply of the mixed salt solution to the reactor was stopped; wherein, the pH value in the reactor was 11, and the concentration of the ammonia water was 0.5 mol / L;
[0149] S2: continuously supplying a fixed amount of aluminum nitrate solution to the reactor to continue the precipitation reaction until the aluminum nitrate solution is completely added;
[0150] S3: Continue to supply the mixed salt solution prepared in step S1 to the reactor for coprecipitation reaction until the particle size Dv50 of the material particles in the reactor reaches 12 μm, centrifuge, wash, filter and dry the reaction slurry to obtain precursor particles.
[0151] S4: LiNi based 0.928 Mn 0.07 Zr 0.002 The precursor particles and lithium hydroxide are mixed in proportion and sintered to obtain the positive electrode active material, wherein the sintering temperature is 700°C, the sintering time is 15h, the heating rate is 5°C / min, the sintering atmosphere is oxygen, and the molar ratio of the aluminum element in the aluminum nitrate in S2 to the total amount of nickel element, manganese element and zirconium element in the S3 mixed salt and the lithium element in the lithium hydroxide is 0.005:1:1.
[0152] (II) Preparation of batteries
[0153] (1) Preparation of positive electrode sheet
[0154] The prepared positive electrode active material, conductive agent acetylene black, and binder polyvinylidene fluoride (PVDF) were mixed in a proper amount of solvent NMP at a mass ratio of 94:3:3, and then coated on both sides of an aluminum foil with a thickness of 13 μm, dried, and cold pressed to obtain a positive electrode sheet. The surface density of the positive electrode sheet coated on one side was 0.02 g / cm 2 ;
[0155] (2) Preparation of negative electrode sheet
[0156] The negative electrode active material artificial graphite, hard carbon, conductive agent acetylene black, binder styrene butadiene rubber (SBR), and thickener sodium carboxymethyl cellulose (CMC-Na) were fully stirred and mixed in a deionized water solvent system according to a weight ratio of 90:5:2:2:1, and then coated on both sides of a copper foil with a thickness of 6 μm, dried, and cold pressed to obtain a negative electrode sheet. The surface density of the negative electrode sheet coated on one side is 0.012 g / cm 2 .
[0157] (3) Preparation of electrolyte: Ethylene carbonate (EC), diethyl carbonate (DEC) and dimethyl carbonate (DMC) are mixed in equal volumes to obtain an organic solvent, and then LiPF6 is dissolved in the organic solvent to prepare an electrolyte with a concentration of 1 mol / L.
[0158] (4) Isolation membrane: A porous polyethylene membrane is used as the isolation membrane.
[0159] (5) Preparation of batteries
[0160] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrodes to isolate them, and then wound to obtain a bare cell. The bare cell is placed in an outer package, injected with a prepared basic electrolyte, and packaged to obtain a full battery.
[0161] Example 2
[0162] The difference from Example 1 is that in step S3, based on LiNi 0.93 Mn 0.07 The nickel element in nickel sulfate and the manganese element in manganese sulfate are mixed in a molar ratio of 0.93:0.07 to prepare a mixed salt solution, and the prepared mixed salt solution is supplied to the reactor to continue the co-precipitation reaction until the Dv50 particle size of the material particles in the reactor reaches 12μm. The reaction slurry is centrifuged, washed, filtered, and dried to obtain precursor particles.
[0163] Comparative Example 1
[0164] The difference from Example 2 is that in step S1 and step S3, both are based on LiNi 0.93 Mn 0.07 The stoichiometric ratio of O2 is 0.93:0.07, and the nickel element in nickel sulfate and the manganese element in manganese sulfate are mixed to prepare a mixed salt solution. See Table 1 for details.
[0165] Comparative Example 2
[0166] The difference from Example 2 is that step S2 is not performed.
[0167] Comparative Example 3
[0168] The difference from Example 2 is that steps S2 and S3 are not performed, and step S1 is: based on LiNi 0.93 Mn 0.07 The stoichiometric ratio of O2 is 0.93:0.07, the nickel element in nickel sulfate and the manganese element in manganese sulfate are mixed in a molar ratio of 0.93:0.07 to prepare a mixed salt solution, sodium hydroxide solution is used as a precipitant, ammonia water is used as a complexing agent, pure water and precipitant are supplied to the reactor, stirring is turned on, and a constant temperature of 60°C is maintained. Stirring is turned on, and the mixed salt solution, precipitant solution and complexing agent solution are supplied to the reactor in a certain flow ratio for co-precipitation reaction, during which the concentration and pH of ammonia water in the reactor are controlled to be constant, and the particle size change of the material particles inside the reactor is monitored until the particle volume particle size Dv50 grows to 12μm; wherein, the pH value in the reactor is 11, and the concentration of ammonia water is 0.5mol / L.
[0169] Example 3
[0170] The difference from Example 1 is that step S1 prepares a mixed salt solution according to the core material shown in Table 1.
[0171] Example 4
[0172] The difference from Example 3 is that step S3 prepares the mixed salt solution according to the shell layer material shown in Table 1.
[0173] Comparative Example 4
[0174] The difference from Example 4 is that step S1 prepares the mixed salt solution according to the core material shown in Table 1, and step S3 prepares the mixed salt solution according to the shell material shown in Table 1.
[0175] Comparative Example 5
[0176] The difference from Example 4 is that step S2 is not performed.
[0177] Comparative Example 6
[0178] The difference from Example 4 is that steps S2 and S3 are not performed, and step S1 is: based on LiNi 0.91 Co 0.07 Mn 0.02 O2 in a stoichiometric ratio, nickel sulfate, manganese sulfate and cobalt sulfate are mixed in a preset stoichiometric ratio to prepare a mixed salt solution, sodium hydroxide solution is used as a precipitant, ammonia water is used as a complexing agent, pure water and precipitant are supplied to the reactor, stirring is turned on, and a constant temperature of 60°C is maintained, stirring is turned on, and the mixed liquid solution, precipitant solution and complexing agent solution are supplied to the reactor in a certain flow ratio for co-precipitation reaction, during which the concentration and pH of ammonia water in the reactor are controlled to remain unchanged, and the particle size change of the material particles inside the reactor is monitored until the particle volume particle size Dv50 grows to 12μm; wherein, the pH value in the reactor is 11, and the concentration of ammonia water is 0.5mol / L.
[0179] Embodiments 5 to 34
[0180] The difference between Examples 5 to 8 and Example 3 is that the core material and shell layer material based on which the mixed salt solution is prepared in Step S1 and Step S3 are different, see Table 1 for details.
[0181] The difference between Examples 9 to 11 and Example 3 is that the amount of aluminum nitrate used in step S2 is different, and the ratio of the total molar number of Al to Li in the prepared positive electrode active material is different, see Table 1 for details.
[0182] The difference between Example 12 and Example 3 is that the core material and shell layer material based on which the mixed salt solution is prepared in step S1 and step S3 are different, and the amount of aluminum nitrate used in step S2 is different, see Table 1 for details.
[0183] The difference between Example 13 and Example 12 is that in step S2, silicic acid (H2SiO3) is used to replace aluminum nitrate, that is, M″ is Si, and the intermediate layer material and the amount of Si are detailed in Table 1.
[0184] The difference between Example 14 and Example 12 is that in step S2, boric acid (H3BO3) is used to replace aluminum nitrate, that is, M″ is B, and the amount of the intermediate layer material and Si is shown in Table 1.
[0185] The difference between Examples 15 to 24 and Example 12 is that the core material and shell layer material based on which the mixed salt solution is prepared in Step S1 and Step S3 are different, see Table 1 for details.
[0186] The difference between Examples 25 to 29 and Example 12 is that the amount of aluminum nitrate used in step S2 is different, and the upper limit and / or lower limit of the distance from the middle layer to the center of the inner core is different, see Table 1 for details.
[0187] The difference between Examples 30 to 31 and Example 12 is that the pH value and the concentration of ammonia water in the reactor are different (the pH value in the reactor in Example 30 is 10.8, and the concentration of ammonia water is 0.8 mol / L; the pH value in the reactor in Example 31 is 11.2, and the concentration of ammonia water is 0.4 mol / L). The values of are different, see Table 1 for details.
[0188] The difference between Examples 32 to 34 and Example 12 is that the core material and shell layer material based on which the mixed salt solution is prepared in Step S1 and Step S3 are different, see Table 1 for details.
[0189] Test method:
[0190] (a) Elemental composition of positive electrode active materials measured by inductively coupled plasma emission spectroscopy
[0191] The instrument standard refers to EPA6010D-2014 "Inductively Coupled Plasma Atomic Emission Spectrometry". The positive electrode active material sample is treated by a chemical method to be digested into a solution, and the atomized plasma is excited to produce characteristic spectral lines of the elements. The element content is qualitatively and quantitatively analyzed according to the wavelength and intensity of the spectral lines (proportional to the concentration), and the relative molar ratio of Li and M" in the positive electrode active materials prepared in each embodiment and comparative example is obtained. The specific operation steps are as follows: Take 0.4g (accurate to 0.0001g) of dry positive electrode active material sample in a 30ml digestion tank, and keep one digestion tank without sample as a blank sample. Move the digestion tank containing the sample into a fume hood and add 12ml of reverse aqua regia. When adding reverse aqua regia, add it along the inner wall of the digestion tank so that the residual sample on the inner wall is washed into the bottom of the tank. Then install the top cover, insulation sleeve, gasket, microwave digestion device, nut in turn, tighten the nut with a wrench, then turn on the microwave digester, and insert the optical fiber sensor in the microwave digester into the previously assembled At the bottom of the digestion tank with the sample, balance and place the digestion tank in the microwave digestion instrument, start digestion (digestion program: 6 minutes to heat up to 120℃ and hold for 8 minutes, 5 minutes to heat up to 160℃ and hold for 8 minutes, 5 minutes to heat up to 180℃ and hold for 5 minutes), cool to room temperature after completion and take out, place the digestion tank in a fume hood, slowly unscrew the nut to release the air, remove the previously installed parts one by one, transfer the solution in the digestion tank to a 100ml volumetric flask through a funnel (filter paper is required), then rinse the digestion tank with ultrapure water, transfer the rinse solution to the volumetric flask, use 10ml of ultrapure water each time, shake the solution in the 100ml volumetric flask, use a pipette to take 1ml of the shaken solution and add it to another 100ml volumetric flask, then add ultrapure water to make up the volume (the total solution reaches 100ml), and finally use ICP-OES (Inductively The sample solution was tested by an inductively coupled plasma optical emission spectrometer. Among them, the reverse aqua regia was prepared by mixing ultrapure water, concentrated nitric acid and concentrated hydrochloric acid in a volume ratio of 4:3:1, and the mass concentrations of concentrated nitric acid and concentrated sulfuric acid were both 68%, which were obtained by purchasing commercial products.
[0192] (b) Test particle size, intermediate layer thickness and position
[0193] With reference to the standard GB / T 19077-2016 / ISO 13320:2009, a laser particle size analyzer was used to calculate the volume particle size distribution of Dv50, Dv90 and Dv10 of the positive electrode active materials prepared in each embodiment and comparative example: (Dv90-Dv10) / Dv50.
[0194] The thickness of the middle layer and the distance from the middle layer to the center of the inner core are determined by the following method: Taking Example 1 as an example, the reaction slurries obtained in steps S1, S2 and S3 are centrifuged, washed, filtered and dried to obtain particles, which are respectively recorded as first particles, second particles and precursor particles. Under the same conditions, lithium hydroxide is mixed and sintered with the particles obtained in steps S1, S2 and S3 according to the same molar ratio of Li and Ni and sintering conditions as in step S4. After cooling, the volume particle size Dv50 of the first particles, the second particles and the precursor particles after sintering with lithium hydroxide is tested by a laser particle size analyzer in accordance with standard GB / T19077-2016 / ISO 13320:2009. Among them, one-half of the volume particle size Dv50 of the first particle after sintering with lithium hydroxide is equivalent to the distance from the inner surface of the intermediate layer to the center of the core, one-half of the volume particle size Dv50 of the second particle after sintering with lithium hydroxide is equivalent to the distance from the outer surface of the intermediate layer to the center of the core, and one-half of the difference between the volume particle size Dv50 of the second particle after sintering with lithium hydroxide and the volume particle size Dv50 of the first particle after sintering with lithium hydroxide is equivalent to the thickness of the intermediate layer. The volume particle size Dv50 (denoted as D1) after sintering the precursor particle with lithium hydroxide is used as a reference to evaluate the distance from the inner surface and outer surface of the intermediate layer to the center of the core and the thickness of the intermediate layer. The method for evaluating the thickness of the intermediate layer and the positional relationship of the intermediate layer in the remaining embodiments and comparative examples is adaptively adjusted with reference to Example 1.
[0195] (c) Characterization of the microstructure of the cut cross section of the positive electrode active material
[0196] The prepared positive electrode sheet is cut by ion beam sputtering to obtain a cross section of the positive electrode sheet. The cross section of the positive electrode sheet is observed by scanning electron microscope to observe the cross section morphology of the cut positive electrode active material particles in the cross section area.
[0197] (d) Initial gram capacity and cycle capacity retention test:
[0198] At a constant temperature of 25°C, let it stand for 5 minutes, discharge to 2.8V at 0.33C, let it stand for 5 minutes, charge to 4.25V at 0.33C, then charge at 4.25V at constant voltage until the current is ≤0.05mA, let it stand for 5 minutes, then discharge to 2.8V at 0.33C. The discharge capacity at this time is the initial gram capacity, recorded as D0. After that, charge to 4.25V at 1C, then charge at 4.25V at constant voltage until the current is ≤0.05mA, let it stand for 5 minutes, then discharge to 2.8V at 1C, the capacity is recorded as D n (n=1, 2...), repeat the previous process to perform charge and discharge cycles, and take the discharge capacity of the 100th cycle as D 100 , 100-cycle discharge capacity retention rate = D 100 / D0×100%.
[0199] (e) Surface test of positive electrode active material particles
[0200] The initial surface condition of the positive electrode active material and the surface cracking condition after 100 cycles of charge and discharge were characterized by a scanning electron microscope. After 100 cycles of charge and discharge, the full battery was disassembled to obtain a positive electrode sheet, the positive electrode sheet was cleaned to remove the residual electrolyte on its surface, the positive electrode sheet was soaked in N-methylpyrrolidone (NMP) until the binder was completely removed, and dried to obtain a powder mixture of a conductive agent and positive electrode active material particles, the powder mixture was sieved or directly characterized (the particle size of the positive electrode active material particles was significantly different from that of the conductive agent), the microstructure of the surface of the positive electrode active material particles was observed and the cracking condition was evaluated, wherein " / " indicates almost no cracking, "+" indicates slight cracking, "++" indicates partial cracking, and "+++" indicates severe cracking.
[0201] (f) Battery volume energy density test
[0202] The obtained battery was subjected to a 0.33C charge and discharge test on a charge and discharge tester. After charging to 4.35V at a rate of 0.33C, the voltage was kept constant until the current was ≤0.05C. The battery was then discharged at 0.33C to 2.8V and the discharge capacity C1 (in Ah) and the discharge voltage V1 (in V) were recorded. The overall volume of the battery was measured to obtain v1 (in L). The volume energy density of the battery = C1×V1 / v1.
[0203] Relevant tests were carried out on Examples 1 to 34 and Comparative Examples 1 to 6, and the test results are shown in Tables 1 to 2.
[0204] Table 1 Differences and test results of Examples 1 to 34 and Comparative Examples 1 to 6
[0205]
[0206]
[0207] Table 2 Differences and test results of Examples 9-12 and 30-31
[0208]
[0209] Results and Conclusions:
[0210] Based on the data of Examples 1 to 34, Comparative Examples 1 to 6 and Table 1, it can be seen that the solution of the above-mentioned embodiments of the present application can effectively improve the cracking of the positive electrode active material during the charge and discharge cycle and improve its capacity retention rate during the charge and discharge process. In addition, when the cross-section of the positive electrode sheet prepared in Examples 1 to 34 is characterized by a scanning electron microscope, it can be seen that the cut positive electrode active material particles in the cross-sectional area have an obvious porous structure between the inner and outer layers (taking Example 1 and Comparative Example 2 as examples, Figure 2 and Figure 3 The cross-sectional views of individual positive electrode active material particles in the positive electrode sheet are shown in Figure 2. Figure 2 and Figure 3 It can be seen that the positive electrode active material of Example 1 has a porous intermediate layer), which further illustrates that there is a porous intermediate layer in the positive electrode active material obtained by the method of the above embodiment of the present application. In combination with Examples 1 to 4 and Comparative Examples 1 to 6, it can be seen that compared with doping the M' element in the core alone or forming the intermediate layer alone, combining the two schemes can also achieve a synergistic effect, which can further improve the cracking of the positive electrode active material during the charge and discharge cycle. In addition, in combination with Examples 1 to 34, it can be seen that the method of the above embodiment of the present application can be applied to different Ni-containing layered positive electrode active materials. Further, in combination with Examples 3 to 4 and 12 to 24, it can be seen that changing the type of M' element and the M" source forming the intermediate layer can also improve the cracking of the positive electrode active material during the charge and discharge cycle and improve its capacity retention rate during the charge and discharge process. Furthermore, in combination with Examples 3 to 11, it can be seen that controlling the doping amount of M' and the M" source forming the intermediate layer relative to the amount of lithium used within the given range is conducive to further improving the cycle capacity retention rate of the positive electrode active material and taking into account a higher energy density. In addition, in combination with Examples 25 to 28, it can be seen that controlling the distance from the inner surface and outer surface of the intermediate layer to the center of the core, and distributing the thickness of the intermediate layer within a given range, is also conducive to further improving the cycle capacity retention rate of the positive electrode active material. Further, in combination with Examples 12 and 30 to 31, it can be seen that increasing the volume particle size distribution width of the positive electrode active material is conducive to further obtaining a higher energy density.
[0211] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A positive electrode active material, characterized in that: include: a core, the core comprising Li a1 Ni x1 M y1 M′ z1 O m1 R n1 , 0.9 ≤ a1 ≤ 1.1, 0.6 ≤ x1 < 1, 0 ≤ y1 ≤ 0.4, 0 < z1 ≤ 0.01, 1.9 ≤ m1 ≤ 2.2, 0 ≤ n1 ≤ 0.1; M comprises at least one element of Co, Mn, Al, Ta, Mg, Mo, Ga, Sn, Ge, Te, La, Ce; M′ comprises at least one element of Y, La, Mo, Zr, W, Sb, Nb, Te, Sr, Ti or Ga; R comprises at least one element of F, Cl or S; An intermediate layer, the intermediate layer covering at least a portion of the outer surface of the inner core, the intermediate layer having a porous structure; The outer shell layer is coated on at least a portion of the outer surface of the intermediate layer, and the outer shell layer includes Li a2 Ni x2 M y2 Mˊ z2 O m2 R n2 , 0.9≤a2≤1.1, 0.6≤x2<1, 0≤y2≤0.4, 0≤z2≤0.01, 1.9≤m2≤2.2, 0≤n2≤0.
1.
2. The positive electrode active material according to claim 1, characterized in that The intermediate layer includes: Mˊˊ p O q , 1≤p≤2, 2≤q≤3, Mˊˊ includes at least one element of B, Al or Si.
3. The positive electrode active material according to claim 2, characterized in that In the positive electrode active material, the ratio of the molar number of the Mˊˊ element to the molar number of the Li element is (0.005-0.02): (0.9-1.1).
4. The positive electrode active material according to claim 3, characterized in that In the positive electrode active material, the ratio of the molar number of the Mˊˊ element to the molar number of the Li element is (0.008-0.012): (0.9-1.1).
5. The positive electrode active material according to claim 1, characterized in that z2>0。 6. The positive electrode active material according to any one of claims 1 to 5, characterized in that The kernel includes: a1 Ni x1 Co y11 Mn y12 Mˊ z1 O m1 R n1 , 0≤y11≤0.2, 0≤y12≤0.2, y11 and y12 are not 0 at the same time; and / or, The outer shell layer includes: Li a2 Ni x2 Co y21 Mn y22 Mˊ z2 O m2 R n2 , 0≤y21≤0.2, 0≤y22≤0.2, y21 and y22 are not 0 at the same time.
7. The positive electrode active material according to claim 6, characterized in that 0.002≤z1≤0.008; and / or, 0.002≤z2≤0.008。 8. The positive electrode active material according to claim 1 or 7, characterized in that: The particle size of the positive electrode active material is D1, the distance from the inner surface of the intermediate layer to the center of the core is greater than or equal to 0.3D1, and the distance from the outer surface of the intermediate layer to the center of the core is less than or equal to 0.4D1; and / or, The thickness of the intermediate layer is 0.05D1 to 0.0625D1.
9. The positive electrode active material according to claim 1 or 7, characterized in that: The volume particle size distribution of the positive electrode active material satisfies: and / or, The volume average particle size Dv50 of the positive electrode active material is 6 μm to 18 μm.
10. A method for preparing a positive electrode active material, characterized in that: include: Mixing the core raw materials including the nickel source, the M source, and the M′ source to obtain a mixed solution, and subjecting the obtained mixed solution to a first precipitation reaction to obtain first particles; Mixing a solution formed by using the intermediate layer raw material with the first particles to perform a second precipitation reaction to obtain second particles; Mixing shell layer raw materials including a nickel source and an M source, and mixing the obtained mixed solution with the second particles to perform a third precipitation reaction to obtain precursor particles; The precursor particles are mixed with a lithium source and sintered to obtain a positive electrode active material; Wherein: the precipitation product formed by the second precipitation reaction on the outer surface of the first particle forms a porous structure through the sintering; The positive electrode active material comprises: a core, the core including Li a1 Ni x1 M y1 M′ z1 O m1 R n1 , 0.9 ≤ a1 ≤ 1.1, 0.6 ≤ x1 < 1, 0 ≤ y1 ≤ 0.4, 0 < z1 ≤ 0.01, 1.9 ≤ m1 ≤ 2.2, 0 ≤ n1 ≤ 0.1; M includes at least one element of Co, Mn, Al, Ta, Mg, Mo, Ga, Sn, Ge, Te, La, Ce; M′ includes at least one element of Y, La, Mo, Zr, W, Sb, Nb, Te, Sr, Ti or Ga; R includes at least one element of F, Cl or S; An intermediate layer, the intermediate layer covering at least a portion of the outer surface of the inner core, the intermediate layer having a porous structure; The outer shell layer is coated on at least a portion of the outer surface of the intermediate layer, and the outer shell layer includes Li a2 Ni x2 M y2 M′ z2 O m2 R n2 , 0.9≤a2≤1.1, 0.6≤x2<1, 0≤y2≤0.4, 0≤z2≤0.01, 1.9≤m2≤2.2, 0≤n2≤0.
1.
11. The method according to claim 10, characterized in that The intermediate layer raw material includes an M" source including a compound having at least one element of B, Al or Si.
12. A positive electrode sheet, characterized in that: include: The positive electrode active material according to any one of claims 1 to 9, or the positive electrode active material prepared by the method according to claim 10 or 11.
13. A battery, characterized in that: Including the positive electrode sheet as described in claim 12.
14. An electrical device, characterized in that: Comprising the battery of claim 13.
Citation Information
Patent Citations
Positive electrode material and preparation method thereof, secondary battery and electric equipment
CN115842117A
Cathode active material and preparation method thereof, secondary battery and electric device
CN115863571A
Positive electrode active material, lithium ion secondary battery and electric equipment
CN115939337A
Cited By
Secondary battery and electric device
CN120854540A